Sailing is Necessary – The allegorical carnivalization of European navigations (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
Just like in theatre, in the parades of the Samba Schools in Rio de Janeiro, multiple systems of meaning compete to promote a complex communication based on signifiers of different code systems. The allegories, among the visual signs presented, stand out for their semantic potential: they are real sets built on wheels that are designed by scenographers and lighting designers to convey the messages intended by the carnival designers. This article analyzes how the same historical event – the so-called Great Navigations – was allegorically approached in the Sambódromo in Rio de Janeiro under different image operations: in representation by similarity, as a sentence-image and as an image without sentence (RANCIÈRE, 2012).
Keywords: navigations; allegories; similarity; sentence-image; image without sentence